Mind-body medicine and altered states of consciousness in Homo - Mohammadi, Kazhaleh; Saniotis, Arthur (Anthropological Review, 2024)
The mind-body relationship has long been a subject of inquiry from both philosophical and scientific perspectives. Ancient Greek philosophers such as Pythagoras and Plato posited dualistic models, where the mind and body are distinct substances. In contrast, modern approaches in Mind-Body Medicine (MBM) offer integrative models that emphasize the interconnectedness of mental and physical states and the proactive role of the patient in their own healing process. This review examines the evolutionary roots of altered states of consciousness (ASC) as a precursor to current MBM techniques. By tracing ASC to early hominins and their cognitive development, it posits that the ability to enter various ASC—such as those used in rituals, meditation, and other mind-body practices—provided evolutionary advantages, influencing both individual fitness and social cohesion. Moreover, this review discusses tonic immobility in animals as a survival mechanism and explores parallels in human and non-human primate behaviors involving ASC. Additionally, neurochemical pathways that govern ASC, such as serotonergic and dopaminergic regulation, are explored for their roles in promoting social behaviors, cognitive flexibility, and emotional regulation. Furthermore, the role of the default mode network is investigated in relation to psychotropic and mood altering substances and altered states of consciousness. This integrated perspective offers new insights into the origins of MBM and underscores the significance of ASC in both evolutionary and contemporary contexts.